Вираження концепту “емоція” в сучасному англомовному дискурсі (на матеріалі жіночих романів 21 століття) - Yesypenko, Nadia (Видавничий дім "Родовід", 2020)
The article analyzes the theoretical and methodological base for the study of emotions and concepts in modern linguistics. The relationship between the conceptual and nominative fi elds is revealed, where the conceptual fi eld has a multilevel structure with the possibility of distinguishing the core, central zone and periphery, and the nominative fi eld of the concept consists of a combination of language means, objectifi es the concept in a certain period of development of society. The conceptual component of the structure of the concept of “emotion” is defi ned. The features of actualization of the concepts of positive and negative emotions in women’s novels by John Green are revealed. The frequency of occurrence of the concepts of positive and negative emotions in the art discourse is analyzed
Keywords: емоція; невербальні засоби спілкування; концепт; концептуальне поле; номінативне поле; понятійний складник